Integração do processo de cristalização de frutose por adição de antissolvente - Crestani, Carlos Eduardo (2012)
Fructose (C6H12O6) is a monosaccharide with increasing industrial interest, and with some advantages over other sugars, facts that have motivated many studies about its production from its aqueous solution, by crystallization. Fructose crystallization occurs, in general, with the addition of ethanol as anti-solvent, aiming the reduction of its solubility and metastable zone width. Addition of ethanol makes feasible fructose crystallization, however, generates other negative factors to the process, as economically, because of its cost, as environmentally, because of the generation of the mother-liquor as a highly concentrate ethanol residue. These factors motivated the study of separation and reuse of the mother-liquor, recycling both ethanol and the diluted solution of non-crystallized fructose back to the process. Besides, the process was integrated into the calcium gluconate enzymatic production, through the reuse of its byproduct as raw material of the process of this work. Because of the absent of experimental data in literature, some methods of calculation of the vapor-liquid equilibrium (VLE) of the ternary solution were tested and compared, providing the choice of some of them to determine the equilibrium data. The method which obtained the best results was the AUNIFAC, and this method was used to provide the energy calculations of the process, by the evaporation and distillation temperature calculations. The cost of energy together with the replaced ethanol, were used to determine the operational cost, allowing the comparison of different operational conditions of the global process. With temperatures above 100°C in laboratorial experiments, the solution became yellow, a behavior of fructose caramelisation. It can occur because of the thermal degradation of fructose producing hydroxymethylfurfural and it prejudices the crystallization process. Because of it, it is necessary to avoid temperatures above 100°C. Finally, the integrated process made feasible crystalline fructose production by crystallization.